Data revolution for agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2015)
As mobile phones, tablets and improved connectivity spread across the world, the amount of data we are gathering and storing is increasing exponentially. With every satellite launch we add further data at ever increasing detail. Knowledge is a core input to agriculture, while data and information are the foundation of knowledge. Is agriculture making the most of the data revolution?